2022
DOI: 10.1038/s41598-022-25792-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress monitoring capability of magnetostrictive Fe–Co fiber/glass fiber reinforced polymer composites under four-point bending

Abstract: Many structural health monitoring (SHM) techniques have been investigated for damage detection in woven glass fiber reinforced polymer (GFRP) laminates. Recently, the GFRP composites integrated with sensors have received attention because the composite material can transmit information about the structural condition during operation. Magnetostrictive materials are considered as feasible candidates to realize the contactless SHM techniques by exploiting the Villari effect, but the theoretical modeling to correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Y_{k} - Y_{\text{N}} \left.\right)}{s_{33}^{\text{f}} \sum_{i = 1}^{11} \left(\left(\right. E_{33} \left.\right)\right)_{i} I_{i}}$$ Table 1 lists the material properties [ 37 ] used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Y_{k} - Y_{\text{N}} \left.\right)}{s_{33}^{\text{f}} \sum_{i = 1}^{11} \left(\left(\right. E_{33} \left.\right)\right)_{i} I_{i}}$$ Table 1 lists the material properties [ 37 ] used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The test results showed that the incorporation of glass fiber improves the mechanical properties and impact resistance of concrete, among which the toughness of concrete is particularly improved. K. Katabira [39] explored contactless structural health monitoring using magnetostrictive materials in glass-fiber-reinforced composite material laminates. They developed magnetostrictive composites, correlated bending stress with magnetic flux density, and validated theoretical models with experiments.…”
Section: Introductionmentioning
confidence: 99%